Respuesta :
In order to find a formula related the v=lwh only to be used to solve for the h value instead of the v value, you would need to isolate the h variable on one side. To do this, divide both sides by lw so that you get a result of h=v/lw which would be your final answer :)
The given equation is:
V = lwh
To be able to solve for h, you will need to isolate "h" on one side of the equation. In order to do so, you will simply divide both sides of the equation by "lw" as follows:
V = lwh
h = (V) / (lw) ..........> equivalent equation solved for h
V = lwh
To be able to solve for h, you will need to isolate "h" on one side of the equation. In order to do so, you will simply divide both sides of the equation by "lw" as follows:
V = lwh
h = (V) / (lw) ..........> equivalent equation solved for h